2020
DOI: 10.1038/s41420-020-00378-9
|View full text |Cite
|
Sign up to set email alerts
|

FN-EDA mediates angiogenesis of hepatic fibrosis via integrin-VEGFR2 in a CD63 synergetic manner

Abstract: Pathological angiogenesis is an important component of hepatic fibrosis along with fibrous deposition, but its role is not well understood. Here, we demonstrated that fibronectin containing extra domain A(FN-EDA), a fibronectin splice variant highly expressed in hepatic fibrosis, mediated angiogenesis in disease progression. FN-EDA was positively correlated with pathological angiogenesis in hepatic fibrosis, and a reduction in FN-EDA expression was associated with diminished intrahepatic angiogenesis and fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Given both NRP1 and NRP2 are known to modulate primary and secondary tumor microenvironments by interacting with integrins to remodel the tumoral ECM ( 20, 64, 66 ), of which FN is known as a major component ( 67 ), it follows that the impaired tumor growth exhibited following NRP codepletion likely arises as a result of perturbations in EDA-FN fibril assembly and deposition. Indeed, EDA-FN has been demonstrated to facilitate tumor growth and invasiveness by promoting matrix stiffness, sustaining tumor-induced angiogenesis and lymphangiogenesis via VEGF-A 165 ( 68 ) and VEGF-C, respectively ( 69 ). For example, Su and colleagues , revealed that EDA-FN secretion promoted VEGFR-2 recruitment to β1 integrin sites, upregulating VEGFR-2 phosphorylation and pathologic angiogenesis during hepatic fibrosis in a CD63-dependent manner ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given both NRP1 and NRP2 are known to modulate primary and secondary tumor microenvironments by interacting with integrins to remodel the tumoral ECM ( 20, 64, 66 ), of which FN is known as a major component ( 67 ), it follows that the impaired tumor growth exhibited following NRP codepletion likely arises as a result of perturbations in EDA-FN fibril assembly and deposition. Indeed, EDA-FN has been demonstrated to facilitate tumor growth and invasiveness by promoting matrix stiffness, sustaining tumor-induced angiogenesis and lymphangiogenesis via VEGF-A 165 ( 68 ) and VEGF-C, respectively ( 69 ). For example, Su and colleagues , revealed that EDA-FN secretion promoted VEGFR-2 recruitment to β1 integrin sites, upregulating VEGFR-2 phosphorylation and pathologic angiogenesis during hepatic fibrosis in a CD63-dependent manner ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, EDA-FN has been demonstrated to facilitate tumor growth and invasiveness by promoting matrix stiffness, sustaining tumor-induced angiogenesis and lymphangiogenesis via VEGF-A 165 ( 68 ) and VEGF-C, respectively ( 69 ). For example, Su and colleagues , revealed that EDA-FN secretion promoted VEGFR-2 recruitment to β1 integrin sites, upregulating VEGFR-2 phosphorylation and pathologic angiogenesis during hepatic fibrosis in a CD63-dependent manner ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given both NRP1 and NRP2 are known to modulate primary and secondary tumour microenvironments by interacting with integrins to remodel the tumoral ECM [20], [45], [47], of which FN is known as a major component [48], it follows that the impaired tumour growth exhibited following NRP co-depletion likely arises as a result of perturbations in EDA-FN fibril assembly and deposition. Indeed, EDA-FN has been demonstrated to facilitate tumour growth and invasiveness by promoting matrix stiffness, sustaining tumour-induced angiogenesis and lymphangiogenesis via VEGF-A 165 [49] and VEGF-C respectively [50]. For example, Su et al ., revealed that EDA-FN secretion promoted VEGFR-2 recruitment to β1 integrin sites, upregulating VEGFR-2 phosphorylation and pathological angiogenesis during hepatic fibrosis in a CD63-dependent manner [49].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, EDA-FN has been demonstrated to facilitate tumour growth and invasiveness by promoting matrix stiffness, sustaining tumour-induced angiogenesis and lymphangiogenesis via VEGF-A 165 [49] and VEGF-C respectively [50]. For example, Su et al ., revealed that EDA-FN secretion promoted VEGFR-2 recruitment to β1 integrin sites, upregulating VEGFR-2 phosphorylation and pathological angiogenesis during hepatic fibrosis in a CD63-dependent manner [49].…”
Section: Discussionmentioning
confidence: 99%
“…In mesothelial cells we found a 3.7-fold upregulation, which is associated with fibrosis in PD patients. KDR was also found to be involved in CKD in general as well as in other indications such as liver disease [36][37][38]. SEMA6D is part of the semaphorin protein family that can act as ligand as well as receptor via reverse signaling [39,40].…”
Section: Receptor-ligand Interactions Between Kdr and Semaphorin 6d (...mentioning
confidence: 99%